Portrait of King Louis XIII of France, 1611, Frans Pourbus the Younger... - Daderot (Wikimedia Commons, 2012)
Notice iconographique issue de Wikimedia Commons. Titre: Portrait of King Louis XIII of France, 1611, Frans Pourbus the Younger - Cleveland Museum of Art - DSC08967.
Droits : Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures